Petrology and phase equilibria of HP/LT eclogite at Gaoqiao, western Dabie and implications for lawsonite development in continental subduction zones - Lu, Xianbin; Xia, Bin; Yang, Qin; Wu, Yuanbao (Frontiers in Earth Science, 2023)
Lawsonite is of great significance for understanding fluid activity, element migration and crust–mantle interactions in subduction zones. Though studies have predicted lawsonite to be present under the P–T regime during continental subduction, no lawsonite has been documented from natural (U) HP rocks in continental orogenic belt. In this study, we work on HP–LT eclogite (GQ–1 and GQ–2) at Gaoqiao, western Dabie to explore lawsonite formation and preservation during continental subduction and exhumation. Both samples have ubiquitous polymineralic aggregates of epidote/clinozoisite + paragonite/albite ± other minerals showing distinct rectangular or rhombic shapes developed as inclusions in garnet or in the matrix. Combined with recalculated bulk compositions similar to that of ideal lawsonite, we interpret these polymineralic aggregates to be pseudomorphs after lawsonite. Phase equilibrium modelling combined with compositional isopleth thermobarometry have constrained a segment of the prograde to peak stages to evolve from 19.0 to 19.5 kbar, ∼470°C to ∼20.0 kbar, 500C–505°C, then to ∼25 kbar, 530C–555°C in lawsonite stability fields. The prograde P–T path shows a two-stage P–T evolution, with the first stage following a geothermal gradient of ∼7°C/km and the second stage decreasing to ∼6°C/km. Initial exhumation was inferred to follow an isothermal decompression process leading to lawsonite breakdown to form epidote/clinozosite ± paragonite via the reaction lawsonite + omphacite→ epidote + glaucophane ± paragonite + H2O at ∼19 kbar, 550°C. Modeled P/T–X pseudosections calculated at T = 550°C and p = 25 kbar show that, when H2O content in bulk composition is more than 1.1 wt%, a certain amount of lawsonite (>13 mode%) should be present in eclogite. On the other hand, in the compositional range of natural intracontinental plate basalts, variations on O (Fe3+), XMgO [MgO/(MgO+FeO)], XCaO [CaO/(CaO+MgO+FeO+MnO+Na2O)], XNa2O [(Na2O/(CaO+Na2O)] and XAl2O3 [Al2O3/(Al2O3+CaO+Na2O)] in bulk compositions have little influence on lawsonite development. In combination with previous studies, we conclude that during continent subduction along low geothermal gradient (<8°C/km), lawsonite could be formed under H2O present conditions. The absence of lawsonite in natural eclogite might be ascribed to retrograde overprint during exhumation.